Democracy and Active Citizen in School Practice - Jarmara, Tomáš (Civilia, 2017)
This article deals with theories of democracy and their application in political practice with regard to level of political participation. Text analysing outputs of repeated international studies focusing on knowledges and attitudes studentes in field of education to citizenship and willingness to civic participation. This text is also focused on possibilities of application and interconnection of tools of direct democracy in municipalities in compliance with curriculum.
Keywords: Theory of democracy; Knowledges and attitudes of students; Curriculum; Forms od direct democracy; Local referendum; Petition; Manifestation; Demonstration